Asuhan Keperawatan Pada Tn. K Dengan Closed Fracture Pelvic Post ORIF di Rumah Sakit Umum Pusat Haji Adam Malik - Cahaya Artha Anastasia Gultom; Dudut Tanjung; Edianto Edianto; Dina Afriani; Saodah Hanin (STIKES Columbia Asia Medan, 2025)
Background: Pelvic fractures are common injuries resulting from high-energy trauma, such as traffic accidents or falls from height. These injuries can cause decreased mobility function, pain, and risk serious complications. A common treatment that can be done is Open Reduction Internal Fixation (ORIF) to improve bone stability and patient mobility function. Objective: this study is to provide nursing care for patients with post-ORIF pelvic fractures to improve nursing outcomes, including pain management, physical mobility, and skin integrity. Methods: This study used a case report approach where the source of research data came from interviews, observations, physical examinations, and patient documentation. Nursing care was organized based on the Indonesian Nursing Diagnosis Standards (SDKI), Indonesian Nursing Intervention Standards (SIKI), and Indonesian Nursing Outcome Standards (SLKI). Results: After the intervention, the patient showed a decrease in pain from scale 6 to scale 3 with the use of PMR. Improved physical mobility was observed through regular ROM exercises, and skin integrity was maintained with position changes and routine wound care. No complications occurred post intervention. Conclusion: Comprehensive nursing care in patients with post-ORIF pelvic fractures can accelerate healing and reduce the risk of complications. Integrated interventions, including pain management, mobility, and skin care, play an important role in supporting patient recovery. The nurse's role in observation and collaboration with the medical team is essential to improve patient outcomes and quality of life.